Contextualising the Female Sublime: A Feminist Reading of Akachi Adimora-Ezeigbo’s House of Symbols (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2026)
Feminism, an ideology which revolves around the refusal by women to be defined by male-established models of femininity, has gone through a lot of mutations. From being an agitation by women for the equality of the sexes, it has graduated to an advocacy for the propagation of a peculiar genre of literature in which women are both the authors and subject matter of the code. The argument for this new mode of literature is that the true identity and potential of women can best be realized when women begin to tell their own stories. This study seeks to establish the plausibility or lack of it of the argument that supports this new mode of female literary identity. Relying on women-centred literary theories such as gynocritics and the female sublime, the study distills the way some female writers are seeking to demolish the structures on which male theory is founded. To bring this to the fore, the study ventures into the audacious province of this new genre of literature that explores female experience from the point of view of female writers. It establishes that the novel under study and its author are products of this radical displacement that is being sought by women. This is done through female characters who reject male codes and patriarchal systems that place women at the lowest rung in the chain of beings. By so doing, they deflect male sexual egos that perceive women as the weaker sex. Through the heroic exploits of her female characters, the author shatters male theories and patriarchal ideologies. The study then submits that the author has not only given impetus to the idea of the female sublime, she has diffused and supplanted the old-fashioned sublime of male domination through female characters who neither subscribe to nor are constrained by any patriarchal ideology.
Keywords: Feminism; Radical; Sublime; Equality; Genre; Codes